Understanding Age‐based Transition Needs: Perspectives from Adolescents and Adults with Congenital Heart Disease. (14th July 2015) - Lopez, Keila N.; Karlsten, Melissa; Bonaduce De Nigris, Francesca; King, Jason; Salciccioli, Katherine; Jiang, Alice; Marelli, Ariane; Kovacs, Adrienne H.; Fordis, Michael; Thompson, Deborah
Abstract: Objective: The purpose of this study was to explore the transition process in congenital heart disease (CHD) care through the perceived needs and concerns of adolescents (pretransition) and the experiential insight from adults (post‐transition), in order to inform future transition initiatives and information delivery methods. Design: In this cross‐sectional study, adolescents and adults with moderate or complex CHD participated in semistructured telephone interviews. Interview transcripts were coded using NVivo qualitative data software. Setting: Single large urban tertiary care CHD center Patients: Adolescents (between 16 and 20 years of age) and adults (21–40 years of age) with moderate or complex CHD. Patients with global developmental delay or known chromosomal abnormalities were excluded. Twenty adolescents and 20 adults participated in the study; each interview allowed for participants to discuss issues relevant to them. Results: Among adolescents, half wanted more CHD information and half were concerned about becoming adults with CHD. All adolescents had access to the Internet via a mobile phone, but only 55% had searched online for CHD information. Adolescents were interested in mentorship with other adolescents (90%) and adults (60%) with CHD either in person or via protected social media. Among adults, 55% were satisfied with the amount of information they had received as adolescents. Areas in which adults would have preferred additional information include longer‐term implications of CHD, employment, insurance, family planning, and mental health. Conclusions: There are similarities and differences in the perceived transition needs of a diverse group of adolescents and adults with CHD. Both cohorts desire additional information during the transition process, including interest in use of a transition checklist to learn about managing their CHD. Adolescents are interested in interactions with other teens and adult mentors with CHD and are open to Internet‐based interventions. Web‐based initiatives could deliver CHD information and provide a platform for social media mentorship.